Penerapan Pasal 262 KUHP Terhadap Pelaku Pengeroyokan Mahasiswa di Universitas Diponegoro - Rif’atul Maula Sya’bani; Sabila Umrotul Hasanah; Cessyda Edyranti Sela; Bunga Swari Pramesti; Jeni Regita Kusuma Cahyani; Dilla Meilani Rahayu (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2026)
Mob violence is a form of violence involving many people, remains a serious problem in law enforcement in Indonesia, particularly in higher education institutions, which should prioritize moral and academic ethics. The case of assault on students at Diponegoro University demonstrates a discrepancy between the legal provisions contained in Article 262 of the Criminal Code and the implementation of the law in the field, particularly in term of the speed and effectiveness of case resolution. This study aims to examine the sequence of events and analyze the application of Article 262 of the Criminal Code to the perpetrators from a legal, social, and human rights perspective. The method used in this study is normative juridical with a statutory, case, historical, and philosophical approach, supported by a literature review and qualitative analysis. The findings of this study indicate that the incident fulfills the elements of criminal act of collective violence as stipulated in Article 262 of the Criminal Code, including the presence of several perpetrators acting simultaneously and causing serious injuries to the victim. However, in practice, various challenges exist, such as difficulty in identifying the roles of each perpetrator, delays in the investigation process, and a lack of coordination among law enforcement. From a social perspective, this incident reflects weak social control and a growing tendency to resolve conflicts outside the legal process. Futhermore, from a human rights perspective, this act represents a violation of the rights to security, equality before the law, and protection from degrading treatment. The implications of this research emphasize the need to improve the effectiveness of law enforcement, strenghthen oversight in academia, and develop policies that provide optimal protection for victims while preventing future collective violence.